Comprehensive analysis of the diatom genus Psammodictyon from Viet Nam: new species, molecular data, and fatty acid content - Kezlya, Elena; Kapustin, Dmitry; Krivova, Zinaida; Maltsev, Yevhen; Nguyen-Ngoc, Lam; Huynh, Duyen Thi Ngoc; Doan-Nhu, Hai; Kulikovskiy, Maxim (Frontiers in Microbiology, 2025)
IntroductionPsammodictyon is a widely distributed marine diatom genus with a complex taxonomy and underestimated species diversity.MethodsLight and scanning electron microscopy, phylogenetic analysis and gas chromatography were used for study of the newly isolated strains of Psammodictyon.ResultsTwelve strains of Psammodictyon were isolated from the coastal waters of central Viet Nam. Based on detailed morphological examinations using light and scanning electron microscopy, as well as molecular phylogenetic analysis, we propose six new species to science. Our phylogenetic analysis indicates that Psammodictyon forms a closely related monophyletic group. The resolution power of the short genetic markers (V4, V9 18S rRNA, V9-ITS1 18S rRNA, and a short region of rbcL), which are widely used for metabarcoding, is also discussed. Analysis of the fatty acid content of seven Psammodictyon strains showed that, like most diatoms, they accumulate high levels of polyunsaturated fatty acids (29.44–42.62%) and monounsaturated fatty acids (20.2–23.2%).ConclusionThe number of known species in the genus Psammodictyon has increased to 21. Psammodictyon strains may be considered as potential producers of long-chain omega-3 polyunsaturated fatty acids.